The Impact of a Principal’s Leadership Style and Teacher Achievement Motivation on Teacher Performance - Chomariah, Chomariah; Lian, Bukman; Wardiah, Dessy (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2022)
The goal of this study was to find out if there is a partial or combined impact of leadership style and teacher achievement motivation on teaching performance. The participants in this study were 70 state junior high school teachers from Palembang City's Jakabaring District. Techniques such as descriptive analysis and data analysis utilizing the SPSS software were applied. According to the findings of the data analysis, the principal's leadership and achievement incentive have a partial and combined influence on teacher performance. This indicates that if the principal's leadership, achievement motivation, and performance continue to rise, with excellent leadership and achievement motivation, teacher performance will undoubtedly improve.